Sistem Penentuan Konsentrasi Jurusan Bagi Mahasiswa Informatika Menggunakan Metode K-Means Di Institut Asia Malang - Puji Subekti; Titania Dwi Andini; Mufidatul Islamiyah (Jurnal Manajemen Informatika (JAMIKA), 2022)
Specialization in the concentration of a major is a student's focus on a particular field of study according to his interests. The purpose of specialization is to focus students more on the knowledge gained from previous courses so that they can be more focused. In the Informatics Engineering study program at the Institute of Asia Malang, there are 3 concentrations, namely: Intelligent Systems; Multimedia and Games and, Computer Network Administration. The absence of a system that helps students choose the concentration of majors is quite difficult for students to know their academic abilities. By looking at these problems, this study aims to build a decision-making system in choosing the concentration of majors using the K-Means Clustering method. Where the data value of semester 1 to semester 4 students is used as a variable in the calculation of the k-means clustering method which is implemented using the PHP and MySQL programming languages. Based on the test results, it was found that in cluster 1 there were 3 students who entered the intelligent system concentration. In the second cluster, there are 20 students who are in the Multimedia and Game concentration, in the third cluster there are 56 students who are in the network concentration.